PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA BIDANG STUDI IPS SEJARAH DI SEKOLAH DASAR - Roni Hamdani, Acep; Subelli, Rijal (STKIP Subang, 2017)
This study aims to: (1) find out whether the discussion method can improve student learning outcomes in the field of study Social Science class V SDN Sukabakti Subang Regency; (2) to describe the steps of applying the method of discussion in improving student learning outcomes in the field of Social Science study of students of grade V SDN Sukabakti Subang Regency. This type of research is Classroom Action Research (PTK), using Suaharsimi Arikunto design. Subjects in this study are the students of grade V SDN Sukabakti Subang Regency which amounted to 27 students. Technique of collecting test data, observation observation, field note, and dokuentasi.tes are used to collect student's cognitive learning data, while observation sheet is used to obtain learning result of afectic aspect, psychomotor, and teacher activity in learning process of Social Science using discussion method. Quantitative decryption analysis techniques to calculate the data of cognitive learning outcomes and qualitative dekristif analysis to mengisisisis data observation results. The results showed that the application of the method of discussion in the field of Social Science study of students in grade V SDN Sukabakti Subang Regency. Based on test results obtained by students at each end of the cycle showed an increase in Social Science learning outcomes. Percentage of completeness on pratindakan by 19%, cycle I by 63% and cycle II by 93%. The process shows that the quality of the learning process becomes increasing, the students look more active, critical, and communicative and susana learning more fun and conducive. In the application of the method of discussion the teacher needs to pay attention to the following matters: (1) to examine the preparations that are deemed to affect the smoothness of the discussion, (2) provide guidance before discussion, (3) implement the rules of discussion according to the rules of the game, 4) Giving equal opportunity to every discussion participant to issue his ideas or ideas, (5) controlling the issue to the subject being discussed, (6) creating a relaxed, fun but controlled learning atmosphere.